2008
DOI: 10.1177/0022185608090000
|View full text |Cite
|
Sign up to set email alerts
|

Employer Matters in 2007

Abstract: The year 2007 may well be remembered as one being short on major industrial disputation, yet one where industrial relations itself dominated public discussion and political life of the country like no other time in Australia's history. It was a year dominated by the electoral cycle, with both organized labour as well as major employers playing their cards very carefully, lest they provide political ammunition to their political and industrial opponents. Thanks largely to the effectiveness of the union movement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The industry was extremely vocal in its opposition to Labor's proposal to scrap the SIAs, and it was reported that both Gillard and Rudd (Grattan, 2007;Norington, 2007) had a number of meetings with industry representatives to alleviate their concerns. Elements of the transitional provisions have been attributed to the extensive lobbying of the industry in opposition to the SIA's removal and consultations with Labor (Hall, 2008;Hearn Mackinnon, 2008;Sutherland, 2009) -although this was denied by the policymakers (ABC News, 2007). The WA mining industry had a much heavier reliance on these agreements than the rest of the Australian economy, hence it was in its interest to utilise the influence it had in this regulatory space to achieve a framework that enabled organisations to preserve what they had.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The industry was extremely vocal in its opposition to Labor's proposal to scrap the SIAs, and it was reported that both Gillard and Rudd (Grattan, 2007;Norington, 2007) had a number of meetings with industry representatives to alleviate their concerns. Elements of the transitional provisions have been attributed to the extensive lobbying of the industry in opposition to the SIA's removal and consultations with Labor (Hall, 2008;Hearn Mackinnon, 2008;Sutherland, 2009) -although this was denied by the policymakers (ABC News, 2007). The WA mining industry had a much heavier reliance on these agreements than the rest of the Australian economy, hence it was in its interest to utilise the influence it had in this regulatory space to achieve a framework that enabled organisations to preserve what they had.…”
Section: Discussionmentioning
confidence: 99%
“…Hence unsurprisingly, the industry was opposed to the removal of SIAs and labelled it akin to 'economic vandalism' (WorkplaceInfo, 2007). Concerns were voiced about the prospect of negotiating with unions and the fear of a re-emergence of industrial action (Hearn Mackinnon, 2008). The industry lobbied to be exempted from the abolition of SIAs (Macdonald, 2007), and it was suggested that Labor made a number of compromises (Sutherland, 2009) to appease the industry.…”
Section: The Context Of Agreement-making In the Wa Mining Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…As is suggested by some of the above statistics, many employers have been concerned at the prospect of union involvement in the bargaining process. One industry that has been the subject of interest in past reviews and has displayed hostility to the changed bargaining arrangements has been the mining sector (MacKinnon, 2008(MacKinnon, , 2009. AMMA has on numerous occasions espoused vociferously their preference for direct employee engagement via individual workplace agreements (Knott, 2009).…”
Section: A New Bargaining Regimementioning
confidence: 99%
“…Employers and employer associations have continued to display major concern about union behaviour in the construction sector (MacKinnon, 2008;Sheldon and Thornthwaite, 2003). In 2009, their concern focused on the proposed amendments to the Building and Construction Industry Improvement Act 2005 embodied in the Building and Construction Industry Improvement Amendment (Transition to Fair Work) Bill: replacing the Office of the Australian Building and Construction Commissioner with the Office of the Fair Work Building Industry Inspectorate; including safeguards on the Inspectorate's powers to obtain information and documents; and establishing the office of the Independent Assessor who may determine upon application that a particular project can be exempt from the examination notice powers.…”
Section: The Construction Industrymentioning
confidence: 99%